Minutes of 3rd technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 3rd Technical and Progress Monitoring (TPM) (session II) meeting of BRACU new campus, held on 10th November, 2018.